UTILIZATION FACILITIES OF PANGKALAN PENDARATAN IKAN (FISH LANDING PORT) AT AIR BANGIS DISTRICT OF WESTPASAMAN, WEST SUMATERA PROVINCE - Hotmaia Harahap; Polaris Polaris; Syaifuddin Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtrakThis research was conducted in August 2017 offish landing portat Air Bangis using survey method. Data analysis using facility requirement analysis and facility utilization analysis.The facilities offish landing portat Air Bangis consist namelyprimary facilities, functional facilities, and supporting facilities. Of the 17 facilities in PPI Air Bangis, 7 facilitiesutilizationwere calculated. The facility utilization rate in PPI Air Bangis ranges from 30.77% to 2,343.50%. Five facilities utilization rate were over its capacity such as the area of the harbor pool, fresh water tank, ice factory, TPI, and the depth of the harbor pool, two facilities that have a utilization rate under its capacity are fuel tank and dock unloading, and one facility not utilized is cold storage facility.Keywords :fish landing port, Air Bangis, utilization rate